Commitment & cooperation in social dilemmas with diverse individual preferences: An agent-based modeling approach. - Zheng Jiang; Luzhan Yuan; Wei Wang; Gaowei Zhang; Yi Wang (PLoS ONE)
Social dilemmas often arise when the need for cooperation conflicts with individuals' incentives to act in self-interest, potentially undermining collective well-being. Prior literature shows that some mechanisms, e.g., commitment, could give rise to cooperation. However, participants' diverse propensities to cooperate may limit such mechanisms' effectiveness. Thus, we bring individual differences in their propensities to cooperate into the reasoning of long-term social dynamics of cooperation through an agent-based modeling (ABM) approach. Our results suggest that commitment may still guarantee cooperation when individuals have different propensities to cooperate but have weaker effects, and the setups of commitment are also important. Our study highlights the importance of integrating individual preferences in analyzing collective dynamics of a population consisting of individuals of heterogeneous characteristics, thus offering implications to facilitate cooperation in real-world online social production. The model and its implementation also form the foundation for supporting decision-makers in forming decisions of facilitating cooperation via commitment mechanisms.